Pengaruh Literasi Dan Perilaku Keuangan Terhadap Keputusan Investasi Masyarakat Kota Palu Di Pasar Modal Dengan Profil Risiko Sebagai Variabel Moderating - Anisa; Jalil, Abdul; Hidayah, Noor Riefma (Journal of Principles Management and Business, 2024)
This study aims to analyze the influence of financial literacy and financial behavior on investment decisions of the people of Palu City in the capital market, while also exploring the role of risk profile as a moderating variable. The study uses Simple Random Sampling to select 100 respondents in Palu City who are involved in capital market investments. Moderated Regression Analysis (MRA) is employed to examine the impact of related variables. The results show that financial literacy has a positive and significant effect on investment decisions, indicating that individuals with good financial understanding tend to make wiser investment choices. Financial behavior also proves to be a significant contributor, affirming that disciplined financial management can enhance investment effectiveness. However, the risk profile does not function as a moderating variable in this relationship, with significance levels suggesting that alignment between risk profile and chosen investment type is often overlooked by the public. These findings highlight the importance of raising awareness about the role of risk profile in investment decision-making, to achieve better investment outcomes in line with individuals' financial conditions.